2003
DOI: 10.2134/jeq2003.2300
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emissions and Soil Indicators Four Years after Manure and Compost Applications

Abstract: Understanding how carbon, nitrogen, and key soil attributes affect gas emissions from soil is crucial for alleviating their undesirable residual effects that can linger for years after termination of manure and compost applications. This study was conducted to evaluate the emission of soil CO2, N2O, and CH4 and soil C and N indicators four years after manure and compost application had stopped. Experimental plots were treated with annual synthetic N fertilizer (FRT), annual and biennial manure (MN1 and MN2, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 27 publications
8
92
3
3
Order By: Relevance
“…Nitrous oxide emissions steadily decreased over the 2-month gas emission measurement period, which accords well with emission trends for land-applied manures reported in the literature (Lessard et al 1996;Chadwick et al 2000;Sherlock et al 2002;Ginting et al 2003;Amon et al 2006;Rochette et al 2008).…”
Section: Clays Decrease Ghg Emissions From Land-applied Manuressupporting
confidence: 88%
“…Nitrous oxide emissions steadily decreased over the 2-month gas emission measurement period, which accords well with emission trends for land-applied manures reported in the literature (Lessard et al 1996;Chadwick et al 2000;Sherlock et al 2002;Ginting et al 2003;Amon et al 2006;Rochette et al 2008).…”
Section: Clays Decrease Ghg Emissions From Land-applied Manuressupporting
confidence: 88%
“…Highest values of microbial activity (PMN) and biomass (MBC, 16S rRNA gene abundance) were found in composted intensive cow manure, suggesting that, when applied to agricultural soil, this amendment could stimulate soil microbial processes, such as, for instance, nutrient cycling. Ginting et al (2003) reported that, 4 years after the last application, compost and manure application resulted in 20-40% higher soil MBC and 42-74% higher PMN, compared with the synthetic N fertilizer treatment.…”
Section: Amendment Qualitymentioning
confidence: 99%
“…This might be due to the continuous application of inorganic fertilizers on conventional farming system increased the nitrogen availability in soil. Table.2 't'-test analysis on effect of cultivation practices of lentil on the incidence of aphid Table.7 't'-test for nutrient status in the soil and nutrient uptake by lentil However, Ginting et al, (2003) reported that the continuous application of organic manures increases the level of N, P and K, in the soil. Singh et al, (2008) reported that the application of FYM, vermicompost and green leaf manures in releasing N and improving N availability in soil.…”
Section: Effect Of Treatments On Availability and Uptake Of Nutrientsmentioning
confidence: 99%